Rancang Bangun Solar Power Meter berbasis Arduino Uno dengan Data Logger untuk Pengukuran Insolasi dan Iradiasi Sinar Matahari - Aris Kiswanto; Hanif Caesar Rachmad; Achmad Solichan; Arief Hendra Saptadi; Dina Mariani; Moh Toni Prasetyo (Institut Teknologi Dirgantara Adisutjipto, 2022)
In planning the installation of solar panels at a location, it is necessary to have solar irradiance data at that location. Solar irradiance data is obtained through direct measurements using a solar irradiance meter. Solar irradiance measuring instruments usually use one of three types of sensors, including thermopile (pyranometer), solar cells, or photodiodes. Each has advantages and disadvantages. The advantages of solar cell sensors are that they have a faster response to sunlight, are more in line with the production of energy produced by solar panels and have a more economical price compared to other sensors. Solar irradiance is directly proportional to the short-circuit current of the solar cell. The aim of this research is to design an Arduino Uno-based device to measure the insolation and irradiance of sunlight, equipped with a data logger to support data analysis. The solar power meter is designed using a solar cell reference with a short circuit current of 455 mA. The microcontroller board used is Arduino UNO ATmega328 while the current sensor used is WCS2801 with a sensitivity of 2mA/mV. Irradiation, current and insolation data are recorded and stored every minute using a datalogger to SD card with a capacity of 16 GB. the average of % error when testing the comparison of readings with photodiode-based solar power meter is 1.747%. The highest point of sun insolation is 5.56.kWh/m2 during three-day period of data logging and it is achieved when solar cell is positioned horizontally on the terrace.